English Teachers’ Readiness in Integrating CTL and Learning and Deep Learning into Language Teaching - Yasminar Amaerita Telaumbanua; Neni Suryani Gulo; Jernita Gulo; Putrawan Saleh Laila; Sevtryani Harefa (Raja Zulkarnain Education Foundation, 2026)
This study aimed to describe English teachers’ readiness in integrating Contextual Teaching and Learning (CTL) and deep learning into English language teaching at the junior high school level. The research participants were ten junior high school English teachers from different schools, selected purposively as research informants. This study employed a qualitative approach with a descriptive design. The primary research instrument was a semi-structured interview, supported by documentation of teaching and learning materials. Data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings revealed that English teachers demonstrated a sufficient level of readiness in integrating CTL by connecting learning materials with students’ real-life contexts. In addition, teachers showed readiness in applying deep learning principles through discussion activities, project-based learning, and collaborative tasks that encouraged students’ critical thinking and communication skills. Supporting factors included the availability of school facilities and teacher collaboration, while challenges involved limited instructional time, differences in students’ language proficiency, and students’ low confidence in using English. The study concludes that the integration of CTL and deep learning has strong potential to enhance the quality of English language teaching when supported by continuous professional development for teachers.